A Tale of Two Shrimps—Speciation and Demography of Two Sympatric Shrimp Species From Hydrothermal Vents - Pierre Methou; Shannon B. Johnson; John Sherrin; Timothy M. Shank; Chong Chen; Verena Tunnicliffe (Molecular Ecology, 2025)
Hydrothermal vents can serve as natural laboratories to study speciation processes due to their fragmented distribution, often with geographic barriers between habitats. Two sympatric species of Rimicaris shrimps occur at vents on the Izu‐Bonin‐Mariana volcanic arc: Rimicaris loihi also occurs near Hawai’i and R. cambonae is present on the Tonga Arc. These two species biogeographically co‐occur and are genetically similar, raising questions about their speciation mechanisms, how they maintain distinct species, and whether interbreeding occurs. Here, we used barcoding and shotgun sequencing to test their genetic isolation and investigate their speciation process. We also evaluated population demography over 10 years to assess population densities and sex ratios at vents. Our results supported R. cambonae and R. loihi as two distinct species despite sympatry throughout part of their range. We also observed regional‐scale genetic structure among R. loihi populations from the Izu‐Bonin‐Mariana volcanic arc, despite high dispersal potential. Finally, we found concomitant variations of shrimp densities and genetic diversity following fluctuations in geological and venting activities over a decade. A combination of geological instability, ocean currents dynamics and sea‐level changes might drive temporary isolation among these local populations. We suggest that similar factors, with longer isolation periods, may also have promoted speciation between the two Rimicaris species, whereas distinct life‐history traits could strengthen and maintain reproductive barriers. Overall, we found that the two species with large geographic distributions had significant patterns of genetic partitioning on a volcanic arc; this scenario contrasts with those observed previously at vents from mid‐ocean ridges or back‐arc basin systems.